Motor Neuron Disease: The Contribution of TAR-43 Gene in Amyotrophic Lateral Sclerosis - Gorky Guha (Bengal Physician Journal)
Motor neuron diseases are a spectrum of neurodegenerative disorders, characterized by their physicochemical propinquity for the voluntary motor systems. The most notorious of these neurodegenerative disorders is amyotrophic lateral sclerosis (ALS), which is a multifocal disorder affecting both lower and upper motor neurons. Amyotrophic lateral sclerosis has been defined as a progressive nervous system disease that affects nerve cells in the brain and spinal cord, causing loss of muscle control. Transactive response element (TAR) DNA binding protein 43 (TDP-43) is an ribonucleic acid (RNA)/DNA binding protein contributing to RNA-related metabolism. Hyperphosphorylated and ubiquitinated TDP-43 deposits function as inclusion bodies in the brain and spinal cord which causes ALS. Majority of the ALS cases are sporadic amyotrophic lateral sclerosis’s (SALS’s) and 5–10% of cases are familial amyotrophic lateral sclerosis (FALS), where mutations of the TDP-43 DNA binding protein (TARDBP) gene occur and the rest (90–95%) are due to mutations in other genes like C9ORF72, SOD1, etc. Whether the ALS is familial or sporadic it has been seen that there is a significant contribution of TDP43 protein in the ALS pathology. Thus, the modality of TDP43-based proteinopathies and its involvement in ALS has been the focal point in the study of ALS-mediated neurodegeneration.